2020
DOI: 10.4132/jptm.2020.05.15
|View full text |Cite
|
Sign up to set email alerts
|

Immune landscape and biomarkers for immuno-oncology in colorectal cancers

Abstract: Colorectal cancer (CRC) is the second most commonly diagnosed cancer and the third leading cause of cancer-related death in Korea [1]. Because of rapid spread of colonoscopy screening, there was a general decrease in CRC until 2010. However, recent studies have reported that the decline in CRC incidence has reversed during the last few years, especially in middle-aged persons, and the occurrence of early-onset CRC has rapidly increased [2]. Most patients with CRC are diagnosed at an operable stage; however, ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 74 publications
1
6
0
Order By: Relevance
“…Similar to the generally accepted subtypes in other cancers, immune subgroups of MSI-H CRCs would be determined by multiple parameters, such as gene signatures, rather than a single discriminating factor. 6 39 This is in line with recent evidence of inconsistency and tumor-type dependency of TMB in immunotherapy responses. 40–42 …”
Section: Discussionsupporting
confidence: 86%
“…Similar to the generally accepted subtypes in other cancers, immune subgroups of MSI-H CRCs would be determined by multiple parameters, such as gene signatures, rather than a single discriminating factor. 6 39 This is in line with recent evidence of inconsistency and tumor-type dependency of TMB in immunotherapy responses. 40–42 …”
Section: Discussionsupporting
confidence: 86%
“…In addition to TMB, several other biomarkers also play an important role in predicting the prognosis of colorectal cancer and the efficacy of ICI. It is reported that these biomarkers overlap in varying degrees in CRC ( 51 ). Although the expression of PD-L1 is considered to be a biomarker for predicting ICI therapy in many cancers (such as lung cancer), current studies have shown that the expression of PD-L1 has no predictive value in CRC patients treated with ICI, and the prognostic value of its overexpression varies with the status of MSI ( 2 , 28 , 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Certain well-documented clinical and histological risk factors are associated with a higher probability of recurrence. In stage III patients and those in stage II with risk factors, adjuvant treatment is recommended to reduce the recurrence risk [ 8 ].…”
Section: Discussionmentioning
confidence: 99%